(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The study is based on the estimation of the main demographic indicators of Nicaragua. It is a descriptive and transversal study. The indicators correspond to the year 20116. Friz and Burgdofer rates indicates that the population of Nicaragua is relatively young, the average age is 23 years and 19 years median. For each active person on the verge of leaving, there is 6 people to point to replace it. There are 6 people that can take care of one person older than 65 years.